CLINICAL AUDIT ON BONE MINERAL DENSITY (BMD) CONDUCTED IN SERDANG HOSPITAL IN THE YEAR 2023 - Chua, Yi Jiang; Parmusuan, Kugnethran; Woon, Yip Xiong; Kan, Meiji; Yap, Xiao Ling; Suen, Jia Wei; Tan, Suzanne; Kaliappan, Shangari; Selvaraj, Vinitha Raj; Samsuddin, Syahrizan (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND BMD measurement using dual-energy x-ray absorptiometry (DXA) remains the gold standard for the diagnosis of osteoporosis. This non-invasive, radiographic test is a convenient tool that guides physicians when to initiate osteoporotic therapy, especially among the elderly population without fragility fracture. METHODOLOGY We conducted a cross-sectional audit on all the BMDs conducted in the year 2023 at HSIS, to study the biodemographics of the patients, severity of BMDs and adequacy of treatment initiated. In this clinical audit, all BMDs were extracted from the electronic medical record (EMR). Medications and bio-demographics of the patients were extracted from the EMR to calculate the FRAX score. RESULTS A total of 473 BMD reports were interpreted. The mean age of the patients was 65.5 (13.4) years while the mean BMI was 25.3 (5.4) kg/m2 . About 89% of patients were female and 11% were male. According to ethnicity, the majority were Chinese (47.4%), followed by Malay (34.7%) and Indian (17.3%). A total of 168 (35.5%) patients who had BMD had a fragility fracture but only 76.2% were treated with anti-osteoporotic agents. Majority of the requests for BMD were from the Orthopaedics Department (57.7%) followed by Rheumatology Unit (23.5%) and Endocrinology Unit (3.6%). About 64.1% (n=303) of patients qualify for antiosteoporotic treatment due to a fragility fracture, a T score ≤-2.5 or osteopenia with FRAX score warranting treatment. However, only 198 (65.3%) were started on anti-osteoporotic treatment. In 165 patients with severe osteoporosis (T score ≤-3.0), only 127 (77%) were started on treatment, and only 2 of them (1.2%) were started on anabolic agents. CONCLUSION Lack of screening, awareness and inadequate funding for anti-osteoporotic treatment were the main contributing factors for delay in treatment or initiation of less potent agents among patients with osteoporosis.